Stability study of darunavir ethanolate tablets applying a new stability-indicating HPLC method - Corrêa, Josilene Chaves Ruela; Serra, Cristina Helena dos Reis; Salgado, Hérida Regina Nunes [UNESP] (Hindawi, 2013)
Chemical and physical degradation of drugs may result in altered therapeutic efficacy and even toxic effects. Therefore, the aim of this work was to study the stability of darunavir and to develop and validate a liquid chromatography (LC) method to determine darunavir in raw material and tablets in the presence of degradation products. The novel method showed to be linear from 6.0 to 21.0 μg/mL, with high precision (CV < 2%) and accuracy (recuperation of 99.64%). It is simple and reliable, free of placebo interferences. The robustness of the method was evaluated by a factorial design using seven different parameters. Forced degradation study was done under alkaline, acidic, and oxidative stress at ambient temperature and by heating. The LC method was able to quantify and separate darunavir and its degradation products. Darunavir showed to be unstable under alkaline, acid, and oxidative conditions. The novelty of this study is understanding the factors that affect darunavir ethanolate stability in tablets, which is the first step to unravel the path to know the degradation products. The novel stability-indicating method can be used to monitor the drug and the main degradation products in low concentrations in which there is linearity.